Study of Strategic Entrepreneurship on Organizational Performance With the Mediating Role of Human Resource Information Systems (study case: Social Security Organization of East Azerbaijan Province) (International Journal of Applied Research in Management and Economics, 2018)
The purpose of this study was to investigate the effect of strategic entrepreneurship on the performance of the organization with the mediator role of human resources information systems. For this purpose, the statistical society of the staff of the Social Security Organization of the East Azerbaijan province was selected. Of all its employees, which was 930 people, 273 people were selected using the Cochran formula as the statistical sample. A questionnaire was used to measure the variables of the research. The results of the analysis of research hypotheses, which were carried out using correlation and structural equations, show that strategic entrepreneurship has a positive and significant effect on the performance of the organization. The role of mediation of human resources information systems in the relationship between strategic entrepreneurship and organization performance was also confirmed. Also, in reviewing research hypotheses, the impact of all the components of strategic entrepreneurship, including entrepreneurial thinking, entrepreneurial culture, entrepreneurial leadership, strategic resource management, creativity, and innovation, was confirmed positively and significantly on human resource information systems and organizational performance.